(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The shape and venation of the metathoracic wings of 94 male scale insects were evaluated. The shape is variable within family and generic levels ranging from elongate and narrow to broadly rounded and wide. The number of veins is reduced consisting of the radial and medial veins in advance taxa, while primitive taxa often have two additional creases representing the position of veins. The two veins in most taxa join at an acute angle in the basal area forrning a basal stem that often extends to the margin. A notable feature is the greater length of this central basal stem from the primitive to advanced taxa.